ADSORPTION CAPACITY OF NATURAL MATERIALS FOR PROCESSING WATERS FROM OIL ACTIVITY TREATMENT - Díaz Rodríguez, Yuletsis; Mendiola Lau, Leonardo; González Suárez, Aimeé; Rivas Trasancos, Lester; Romero Silva, Roberto (Centro Azúcar Journal, 2021)
Introduction: Current applications for liquid waste treatment are directed towards the study of new renewable materials, with high availability to be used as supports that act as a natural filter with very high porosity and adsorbent properties. The wastewaters of the oil activity complex composition demands the adoption of methods that use more efficient adsorbent materials to facilitate the management and final disposal of its effluents. Objective: To determine the apparent adsorption capacity of different natural materials for the treatment of oil activity wastewater. Materials and Methods: The contamination indicators determined were the Chemical Oxygen Demand, sulfides, fats and oils, for which international APHA and ISO standards were used, as well as the adsorption and kinetic isotherms of materials such as sugarcane bagasse, rice straw, agromena, zeolite and active mud. Results and Discussion: All the materials presented the highest adsorption capacity after 20 min of contact, with values of this parameter standing out for COD of 67 and 70 mg/g with bagasse and rice straw; and removals greater than 95% for sulfides, fats and oils with all materials. Conclusions: The highest values of COD adsorption capacity (26-63 mg/g) and sulfides (10-12 mg/g) were reached at 20 min of contact with the residual and under packing conditions, the best results correspond to bagasse cane, rice straw and improver product.